Negative differential resistance in graphene nanoribbon superlattice field‐effect transistors. (1st August 2015) - Chang, Sheng; Zhao, Lei; Lv, Yawei; Wang, Hao; Huang, Qijun; He, Jin
Abstract : Different from researches in two‐terminal nanoscale graphene structures, the negative differential resistance (NDR) phenomenon in graphene nanoribbon superlattice (GNSL) field‐effect transistors (FETs) is studied in this reported work. Numerical analyses of two types of GNSL FETs with different gate voltages reveal that NDR occurs in some 'Z'‐type GNSL FETs under some gate voltages, which develops NDR research compared with the traditional two‐terminal nanoscale structures. Based on these results, two trends are observed: the 3 m + 2 series GNSL FETs easily exhibit NDR, whereas it is more difficult to achieve this phenomenon with narrow FETs. This phenomenon is explained by the transmission coefficient as well as ab‐initio calculations of the energy levels, where the entire channel of the FET is considered as a supercell. Through this analysis, the effect of gate control on energy‐level localisation is uncovered, and a heterojunction‐like explanation is proposed. This new explanation bridges the gap between a novel structure's physical analysis and the general semiconductor device concept, which can also provide inspiration for improving our understanding of novel nanostructure devices.